P830 Motherhood and child care are negatively influenced by ulcerative colitis: patients' insights from the UC-LIFE survey. (16th January 2018) - Carpio, D; Argüelles-Arias, F; Calvet, X; Cea-Calvo, L; Juliá, B; Romero, C; López-Sanromán, A
Abstract: Background: Surveys to patients complement information from clinical studies. In this work, we describe the insights of patients with regard to the perceived impact of ulcerative colitis (UC) on their decision to have children and on the vitality to take care of them. Methods: The insights were collected through an anonymous survey from consecutive UC patients >18 years from 38 hospital clinics in Spain. Patients completed the survey at home and returned it by pre-paid mail. Patients responded "yes/no" to the following questions (1) "Do you think your UC has influenced your decision to have children?", and (2) "In case you have children, do you feel your UC influences your vitality to take care of them?" The chi-squared or Fisher exact tests were used for the comparison of proportions between the responses in different subgroups. Results: 585 patients received the survey, 436 (74.5%) returned it (mean age 46.2 years, 52.8% men and 47.2% women, median duration of UC 8 years). Sixty-nine percent were married or living with partner. Patients described the UC symptomatic burden as: "symptoms controlled" (47.1%), "symptoms not impairing everyday life" (28.0%) and "symptoms impairing everyday life" (24.9%). Excluding patients who responded that questions (1) and (2) did not apply to them ( n = 126 and n = 147, respectively), 48 out of 278 patients (17.2%) reported that UC had influenced their decision to have children, and 104 of 255 (40.8%) agreed that UC influences their vitality to take care of them. The percentages were higher in women than in men, in younger patients and in those who described more symptomatic disease (Table). Conclusions: Patients acknowledge a negative impact of UC on critical decisions like motherhood and on the vitality to take care of children, especially women, younger patients and those who report a higher symptomatic burden. Acknowledgments. Funded by Merck Sharp & Dohme of Spain and endorsed by ACCU (Confederation of Spanish associations of patients with Crohn's disease and ulcerative colitis).